BIOTEKNOLOGI DAN BIOETIKA: CETAK BIRU UNTUK MASA DEPAN UMAT MANUSIA - Fahri, M (Jurnal Bestari, 2001)
The latest result of biotechnology always arise pro and contradictions. It does not only gives hope and chance in the promising future, but also has some dangerous problems for a dunty of humanity. However, biotechnology is ambigous that includes positive and negative effects. The benefits can widen and hazard can also minimize, when biotechnology goes on the ethic, morality, culture, and religious norm. The bioethic eventually has to guide the independently valued biotechnology during its development can run well and avoid into turbulence/trouble. This article wants to attend biotechnology before bioethic